High-Throughput Dissolution/Permeation Screening —A 96-Well Two-Compartment Microplate Approach - Ann-Christin Jacobsen; Anna Krupa; Martin Brandl; Annette Bauer-Brandl (Pharmaceutics, 2019)
Early formulation screening can alleviate development of advanced oral drug formulations, such as amorphous solid dispersions (ASDs). Traditionally, dissolution is used to predict ASD performance. Here, a high-throughput approach is described that simultaneously screens drug dissolution and permeation employing a two-compartment 96-well plate. Freeze-drying from hydro-alcoholic solutions was used to prepare amorphous formulations. The screening approach was tested on amorphous and crystalline tadalafil formulations with and without Soluplus®. The workflow consisted of: 1) dispersion of the formulations; 2) incubation within the two-compartment plate, where a dialysis membrane separated donor (dispersed formulation) and acceptor; 3) sampling (donor and acceptor), where donor samples were centrifuged to remove non-dissolved material; and 4) quantification by UHPLC-UV. To identify optimal screening conditions, the following parameters were varied: dispersion medium (buffer / biomimetic media), acceptor medium (buffer / surfactant solutions), and incubation time (1, 3, and 6 h). Surfactants (acceptor) increased tadalafil permeation. Biomimetic medium (donor) enhanced dissolution, but not permeation, except for freeze-dried tadalafil, for which the permeated amount increased. The predictiveness was evaluated by comparing dissolution-/permeation-results with in vivo bioavailability. In general, both dissolution and permeation reflected bioavailability, whereof the latter was a better predictor. High-throughput dissolution/permeation is regarded promising for formulation screening.